IDENTIFIKASI DIFFERENTIAL ITEM FUNCTIONING PADA TES PENGERTIAN MEKANIK (C4) DENGAN PENDEKATAN RASCH MODEL - Prahastuti, Nurul F (Universitas Sahid Surakarta, 2022)
Mechanical Reasoning Test (C4) was used in an assessment to measure the mechanical reasoning aptitude. Mechanical Reasoning Test has a quality of high-stakes exam, it has a major life consequence for the subject. Mechanical Reasoning Test needs to be re-tested to check whether its items’ usage are still justified or if it needs to be changed. Also, besides having good items qualities, it is also important to make sure that Mechanical Reasoning Test (C4) are not biased for one gender. An item indicated to be DIF will be beneficiary for one group of subjects, while biased against another. The purpose of this research was to test the quality of items and to identify the Differential Item Functioning (DIF) of Mechanical Reasoning Test using Rasch Model. Rasch Model was chosen because it has advantages in data analysis compared to classical model. Data analysis was done using the software Winstep 3.73. The amount of data gathered were 528 divided into M = 184 and F = 344. Respondents’ age range was 16 to 20 years old. The analysis showed that Mechanical Reasoning Test was a difficult test, because the difficulty level was much higher than subjects’ capability. The reliability score was .73, as such it can be considered reliable. All the questions in Mechanical Reasoning Test were fit and can show subjects’ true capability. There were 24 items indicated to be DIF and biased for one group of subjects.